Design, synthesis and in silico molecular modelling studies of 2-Hydrazineyl-2-oxoethyl-4-(1H-pyrrol-1-yb) benzoate derivatives: a potent dual DHFR and ENR-reductase inhibitors with antitubercular, antibacterial and cytotoxic potential - Mater H. Mahnashi; Prem Kumar Santhemavathuru Ramachandraiah; Ahmed Abdullah Al Awadh; Ibrahim Abdullah Almazni; Yahya I. Asiri; Ibrahim Ahmed Shaikh; Basheerahmed Abdulaziz Mannasaheb; Sravanthi Avunoori; Aejaz Abdullatif Khan; Shrinivas D. Joshi (PLoS ONE, 2025)
The current research includes the study of 28 new 2-hydrazineyl-2-oxoethyl-4-(1H-pyrrol-1-yl) benzoate derivatives as antitubercular, antibacterial, and enoyl-ACP reductase enzyme inhibitors. SYBYL-X.2.0 was used to investigate the molecular docking of ENR-ACP reductase/InhA in complex with 1-cyclohexyl-N-(3,5-dichlorophenyl)-5-oxopyrrolidine-3-carboxamide (PDB ID:4TZK) and MtDHFR in complex with methotrexate (PDB ID:1DF7). All of the reported derivatives have two or more H-bonding interactions with TYR158 and the cofactor NAD + , which fit snugly into InhA’s binding pocket, with MIC values of 0.8–3.12 µg/mL, 0.4–3.12 µg/mL, and 1.6–12.5 µg/mL [4(a-e), 5(a-p), 6(a-e)]. Also, the molecular H-bonding interactions of reported molecules with amino acids ARG32 and ARG60 of MtDHFR showed the interaction of molecules with targeted site. All of the reported compounds showed good activity against M. tuberculosis H37Rv, Gram-negative E.coli, and Gram-positive S. aureus, respectively. Compounds 5b and 6d showed highest antitubercular activity with the MIC value of 0.8 µg/mL. InhA inhibition was good to moderate in the tested compounds, with IC50 inhibition ranging from 9 to 51% at 50μM; and MtDHFR inhibition was good with IC50 values ranging from 23 to 153 µM compared to trimethoprim at 92 µM. The most potent compounds exhibiting dual enzyme inhibition were further evaluated for cytotoxicity in mammalian cells using the human lung cancer cell line A549. These compounds demonstrated significant cytotoxic effects, with IC50 values ranging from 255 to 319 µg/mL. In comparison, the standard antitubercular drug isoniazid exhibited an IC50 value greater than 450 µg/mL, while the anticancer drug cisplatin showed an IC50 value of 9.9 µg/mL. These molecules represent excellent future therapeutic possibilities with potential use in the biological and medical sciences due to the compounds’ pronounced docking properties and biological activity.